1998
DOI: 10.1083/jcb.143.2.297
|View full text |Cite
|
Sign up to set email alerts
|

Serine Phosphorylation of SR Proteins Is Required for Their Recruitment to Sites of Transcription In Vivo

Abstract: Expression of most RNA polymerase II transcripts requires the coordinated execution of transcription, splicing, and 3′ processing. We have previously shown that upon transcriptional activation of a gene in vivo, pre-mRNA splicing factors are recruited from nuclear speckles, in which they are concentrated, to sites of transcription (Misteli, T., J.F. Cáceres, and D.L. Spector. 1997. Nature. 387:523–527). This recruitment process appears to spatially coordinate transcription and pre-mRNA splicing within the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
202
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(216 citation statements)
references
References 59 publications
(127 reference statements)
14
202
0
Order By: Relevance
“…In two cases, a single species of pre-mRNA has been followed from its transcription site to the nuclear pore, and in neither case did the RNA seem to accumulate in nuclear subcompartments (Singh et al, 1999;Shav-Tal et al, 2004). Instead, it seems that splicing components typically move away from speckles to sites of gene expression where splicing occurs cotranscriptionally (Huang and Spector, 1996b;Misteli et al, 1997Misteli et al, , 1998Eils et al, 2000). These findings have therefore made it difficult to understand why poly(A) RNA is associated with speckles.…”
mentioning
confidence: 73%
“…In two cases, a single species of pre-mRNA has been followed from its transcription site to the nuclear pore, and in neither case did the RNA seem to accumulate in nuclear subcompartments (Singh et al, 1999;Shav-Tal et al, 2004). Instead, it seems that splicing components typically move away from speckles to sites of gene expression where splicing occurs cotranscriptionally (Huang and Spector, 1996b;Misteli et al, 1997Misteli et al, , 1998Eils et al, 2000). These findings have therefore made it difficult to understand why poly(A) RNA is associated with speckles.…”
mentioning
confidence: 73%
“…For example, splicing factors could be released from the speckles, where they are stored. It has been demonstrated that CLKs regulate the intranuclear localization of SR proteins (Duncan et al, 1998;Nayler et al, 1998b) and that phosphorylation of the RS domain is necessary for targeting SR proteins to sites of transcription (Misteli, 2000;Misteli et al, 1998). To test this hypothesis, we compared the effect of several proteins that are phosphorylated by CLKs in vitro with the CLK effect on exon 10 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This process appears to be controlled by protein phosphorylation Misteli, 1999); serine-arginine (SR) proteins, a major constituent of IGs (Mintz et al, 1999), are phosphoproteins containing a C-terminal serine-arginine rich RS domain and N-terminal RNA recognition motifs (RRMs; for review, see . Experiments monitoring GFP-tagged SF2/ASF SR protein in living cells have shown that phosphorylation controls the movement of SR proteins from speckles to sites of active transcription (Misteli et al, , 1998. Similarly, in vitro and in vivo studies using several kinases indicate that phosphorylation of SR proteins releases them from IGs (for review, see Stojdl and Bell, 1999), whereas phosphatases have an opposite effect (Misteli and Spector, 1996).…”
mentioning
confidence: 99%
“…Similarly, in vitro and in vivo studies using several kinases indicate that phosphorylation of SR proteins releases them from IGs (for review, see Stojdl and Bell, 1999), whereas phosphatases have an opposite effect (Misteli and Spector, 1996). Therefore, it has been proposed Misteli et al, 1998;Stojdl and Bell, 1999) that the recruitment of splicing factors from speckles occurs in two steps. First, SR proteins are physically released from speckles via RS domain phosphorylation.…”
mentioning
confidence: 99%